Gut microbiota-derived extracellular vesicles: novel perspectives from host-microbe interactions to therapeutic applications - Yuwei Han; Yuying Guo; Wenzhe Xu; Yunsha Zhang; Hongying Hao; Yanhong Song; Nanjin Yu; Linna Zhao; Shixin Xu (Journal of Physiology and Biochemistry, 2026)

Biomimetic hybrid fibers integrate scaffold topology and bioinert protein cues to harmonize microglial phagocytosis and anti-neuroinflammation - Ming Yin; Chenlong He; Yuwei Wang; Jingwen Qin; Huawei Liu; Han Zhou; Hongyi Zhang; Shan Hua; Shengming Wu; Jing Chen; Keyue Xiao; Qihui Wu; et al. (Chemical Engineering Journal, 2026)

Unveiling the transformation patterns and mechanisms of organic micropollutants and wastewater effluent organic matter during UV222-based oxidation systems - Yuwei Xie; Han Su; Yuan Zhang; Wenzheng Chen; Félix Manuel Rosado-García; Xin Yu; Mingbao Feng (Water Research, 2026)

Potential Causes of Anti‐Phase Summer Precipitation Variability Between the Middle and Lower Reaches of the Yangtze River - Yuwei Zhou; Ge Liu; Xiaolu Yan; Sulan Nan; Ting Zhang; Yinghan Sang; Xuefeng Han; Yuhan Feng; Hancheng Zou (International Journal of Climatology, 2026)
Summer precipitation in the middle and lower reaches of the Yangtze River generally shows synchronous variability and is thus extensively studied as a unified climatic region. However, out‐of‐phase variations occur between the middle and lower reaches in some years. This study investigates the mechanisms of the positive middle Yangtze River precipitation (MYRP)–negative lower Yangtze River precipitation (LYRP) pattern from the perspectives of atmospheric circulation and land‐ocean thermal anomalies. The results suggest that a non‐canonical Silk Road Pattern (SRP) teleconnection in the upper troposphere, coupled with a mid‐to‐lower tropospheric anomalous anticyclone over Northeast Asia and a weakened western Pacific subtropical high (WPSH), contributes to this precipitation pattern. Further analysis reveals that colder‐than‐normal land thermal anomalies in the Greater Caucasus Mountains and the northeastern Tibetan Plateau, as well as warmer‐than‐normal sea surface temperature anomalies (SSTAs) in the Sea of Japan, may help maintain the SRP‐like Rossby wave train (SLWT), therefore influencing the positive MYRP–negative LYRP pattern. Linear baroclinic model sensitivity experiments further support the identified thermal anomalies can excite and maintain the SLWT. Given that the SLWT differs to some extent from the classical SRP in both wave source and downstream structure, this study also proposes a SLWT index based on 200‐hPa vorticity anomalies. This index effectively captures both the spatial structure of the SLWT and its link with out‐of‐phase precipitation anomalies between the middle and lower reaches of the Yangtze River and may serve as a potential indicator for the occurrence probability of the positive MYRP–negative LYRP pattern. These findings may improve our understanding of regional precipitation mechanisms in the Yangtze River basin, thereby providing a scientific basis for improved disaster prevention and mitigation strategies.

High-efficiency sea urchin-like α-Fe2O3 nanoflower cathode for electrosorption of uranium(VI) - Hongyan Zhou; Ranran Jiao; Xiaotong Ma; Junyue Han; Suyuan Zeng; YuWei Mi (Journal of Environmental Chemical Engineering, 2026)

Influences of environmental factors on the microbial community characteristics of bioaerosols in a cold region - Nami Lai; Shuozhen Tian; Silu Wang; Xiaoyan Wang; Ruihan Chen; Yuwei Liu; Huize Yang; Mengying Wang; Xiaoyu Cai; Wanying Yao; Shuling Li; Yue Xiao; et al. (Journal of Environmental Sciences, 2026)

Phosphorus source-sink distributions and fluxes in shallow-water wetland sediments: Insights from multiple habitats, varying water quality, and microbial communities - Yuwei Zhang; Shengqi Zhang; Yangyang Han; Cheng Guo; Ling Liu; Hongjie Wang (Journal of Environmental Sciences, 2026)

Seafloor topographic modulation of sediment dispersal and polymetallic nodule genesis in the western Clarion-Clipperton Zone (CCZ), Pacific Ocean - Zeren Zhang; Zhenggang Li; Hao Wang; Xibin Han; Yuwei Liu; Xuan Zeng; Yanhui Dong; Zhimin Zhu; Kehong Yang; Jie Li; Huaiming Li; Xiaohu Li (Marine Geology, 2026)

Global Warming Amplifies Nitrogen Over Phosphorus Limitation in Aquatic Ecosystems: A Multi‐Trophic Meta‐Analysis - Misha Zhong; Ping Xie; Yuhao Feng; Wenxuan Han; Enzai Du; Di Tian; Ruijing Ma; Yuwei Wang; Zengliang Jian; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; et al. (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) availability fundamentally regulate the structure and function of aquatic ecosystems. While global‐scale patterns of relative nutrient limitation have been increasingly documented, their responses to climate warming remain poorly quantified. To address this, we integrated a global meta‐analysis of nutrient enrichment experiments (spanning 510 sites and multiple trophic levels) with large‐scale datasets of water chemistry from 3403 lakes and 13,032 marine sites. Meta‐analysis showed that primary producers have the strongest responses to nutrient enrichment, especially NP co‐addition, with effects attenuating at higher trophic levels. Increasing temperature amplifies the response of primary producers to nutrient enrichment, but not for consumers, indicating that warming disrupts energy flow to higher trophic levels. Furthermore, relative N limitation of primary producers intensifies with increasing temperature and decreasing latitude in both freshwater and marine ecosystems. Global field observation of water chemistry supports such a pattern as water N:P mass ratios decrease with increasing temperature across lake and marine ecosystems. Our findings provide robust empirical evidence that the relative nutrient limitation of primary producers exhibits a strong latitudinal gradient and climate warming could fundamentally enhance nitrogen over phosphorus limitation in aquatic ecosystems, which have critical implications for ecosystem functioning and management in a warmer world.

Spatiotemporal evolution and driving mechanisms of hazardous air pollutants and greenhouse gas emissions from China's copper industry - Lu Chen; Yuwei Zhao; Feng Han; Yuzhao Cui; Huiying Yang; Huitian Duan; Shuai Li; Xiaowei Cui; Wei Liu; Zhaojie Cui (Journal of Cleaner Production, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Long-term nitrogen deposition suppresses microbial necromass carbon with depth- and season-specific patterns in forest soils - Chen Zhang; Juanping Ni; Xiaoming Zou; Han Y.H. Chen; Yuwei Liu; Ke Shi; Tingting Ren; Guobing Wang; Honghua Ruan (Soil and Tillage Research, 2026)

Harnessing the application of functional polysaccharides in food packaging - Yuwei Wang; Hailong Bai; Shunjiang Jia; Qiao Zhang; Peng Zhao; Yuping Tang; Lizeng Peng; Elaine Lai-Han Leung (Trends in Food Science & Technology, 2025)

Water migration and browning mechanisms in postharvest litchi pericarp: Insights from LF NMR - Yongqi Chen; Jingyi Li; Difa Zhu; Dongmei Han; Chulin Zhou; Yao Li; Yiwen Liu; Yuwei Ma; Tao Luo; Bingyi Wen; Zhenxian Wu (Postharvest Biology and Technology, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

DDX3X Aggravates Neuronal Pyroptosis and Inhibits Autophagy via NLRP3 Inflammasome After Experimental Subarachnoid Hemorrhage - Guangzhi Hao; Yu Huan; Yuwei Han; Zuolin Shi; Xinyu Yang; Yushu Dong; Pengyu Pan; Guobiao Liang (Molecular Neurobiology, 2025)

Novel alkali-resistant nitrogen and phosphorus removal strain I4: Performance evaluation and molecular mechanism - Xiaoxuan Fan; Jiayi Zhou; Qionghua Chen; Yuwei Feng; Ruirui Han; Guangfeng Chen; Sha Yue; Yonghao Ma; Hu Shu (Bioresource Technology, 2025)

Effects of compound probiotics on intestinal and liver transcriptome, immunity and disease resistance of zig-zag eel (Mastacembelus armatus) - Yuwei Feng; Yiman Chen; Zhiting Zuo; Xianshan Lin; Qiaoyi Chen; Along Gao; Zhide Yu; Chong Han; Hu Shu (Aquaculture, 2025)

Efficiency and mechanism of iron sludge-derived magnetic adsorbent for purifying organic-complexed high-arsenic groundwater - Huiping Zeng; Su Han; Weihua Zhao; Yuwei Zeng; Jiongru Liang; Xiaoying Zheng; Dong Li; Jie Zhang (Journal of Environmental Chemical Engineering, 2025)

Target mitochondrial pyroptosis with sequential delivery of nanoliposomes to alleviate secondary injury following traumatic brain injury - Yuwei Lin; Jiaqi Jin; Qingyi Han; Diancheng Hang; Zijun Chen; Suihan Ye; Qing Guo; Xuyang Huang; Jinna Li; Hengzhu Zhang; Xuefeng Zhang; Yufu Zhu (Chemical Engineering Journal, 2025)

Restoration of mitochondrial homeostasis by Wnt3a/β-catenin/c-Myc alleviates cadmium-induced neural stem cell senescence and cognitive impairment in mouse hippocampus - Yuwei Zhang; Qiuyun Gu; Yixi Li; Jiayi Li; Yaxin Han; Longfei Feng; Xutong Qin; Jiming Zhang; Zhijun Zhou; Xiuli Chang (Journal of Hazardous Materials, 2025)

Direct ammonia oxidation colony-driven DAAO process: construction strategy and optimization of denitrification efficacy - Yuwei Mi; Dingqiu Wei; Shuangjiang Liu; Defeng Li; Han Chen; Yijie Zheng; Mingming Chen; Dongru Qiu; Renbing Bao; Jian Xu; Zhiquan Hu (Chemical Engineering Journal, 2025)

Ionic liquid-functionalized metal-organic frameworks adsorbents for effective extraction of dibutyl phthalate in edible oil: A new strategy for selectivity and low cost - Qian Yang; Yuwei Zhang; Lei Han; Jun Sheng; Yang Tian (Food Chemistry, 2025)

Mechanistic insight into enhancement of undissolved rice husk biochar on Tetracycline biodegradation by strain Serratia marcescens basing on electron transfer response - Siyu Wang; Jie Han; Ziyi Ge; Xu Su; Yongjia Shi; Fan Xia; Yuwei Huang; Jun Meng (Journal of Hazardous Materials, 2025)

Establishing g-C3N4-Vn/FeIn2S4 heterostructure for in-situ H2O2 generation and activation to degrade tetracycline in photo-Fenton process under visible light - Rui Han; Yuwei Yao; Tadayuki Fujii; Yasushi Iseri; Xiaobiao Zhu (Environmental Research, 2025)

Amplified tibetan plateau surface warming in CO2-induced global warming simulations - Yuwei Wang; Zhenghui Lu; Ziqian Wang; Fei Huang; Jingchuan Zhao; Han Huang; Jing Feng; Yi Huang (Climate Dynamics, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Petrogenesis of Chang'E-6 basalts and implication for multi-episode volcanism in the lunar farside basin - Dehan Shen; Shijie Li; Shaolin Li; Yingkui Xu; Yang Li; Mingbao Li; Deliang Wang; Ronghua Pang; Yuwei Zhang; Zhipeng Han (Earth and Planetary Science Letters, 2025)

Increased spike density and enhanced vegetative growth as primary contributors to improvement of dryland wheat yield via surface mulching - Yuwei Chai; Yawei Li; Rui Li; Lei Chang; Hongbo Cheng; Jiantao Ma; Yuqing Qin; Fanxiang Han; Changgang Yang; Yuzhang Chen; Qian Chen; Yao Zhang; et al. (Field Crops Research, 2025)

Use quercetin for pulmonary fibrosis: a preclinical systematic review and meta-analysis - Xuanyu Wu; Xiang Xiao; Yuchen Su; Yuwei Zhang; Ganggang Li; Fei Wang; Quanyu Du; Han Yang (Inflammopharmacology, 2025)

Plasma Extracellular Matrix Protein 2 Level as a Predictive Biomarker for Rupture of Small Intracranial Aneurysms - Chenchen Wang; Yuwei Han; Da Huo; Xiaoming Li; Guobiao Liang (Journal of Molecular Neuroscience, 2025)

Degradation of myosmine by a novel bacterial strain Sphingopyxis sp. J-6 and its degradation pathways - Bingjun Dang; Hui Gao; Wei Jia; Yuwei Zhang; Zicheng Xu; Dan Han; Jinchu Yang; Yao Huang; Zheng Chen; Yadi Wang; Yingqiu Duan; Ruohua Yuan; et al. (Journal of Hazardous Materials, 2025)

Microporous carbon derived from waste plastics for efficient adsorption of tetracycline: Adsorption mechanism and application potentials - Shiyu Bian; Zhuoyu Cai; Weinan Xing; Chunyu Zhao; Yuwei Pan; Jiangang Han; Guangyu Wu; Yudong Huang (Environmental Research, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Antibacterial mechanism of atmospheric cold plasma against Pseudomonas fluorescens and Pseudomonas putida and its preservation application on in-packaged red shrimp paste - Jiajie Hu; Yao Zhang; Weicong Pan; Qianyun Han; Yu Wei; Yuwei Li; Yi Hu; Xiaoguo Ying; Andrea Armani; Alessandra Guidi; Shanggui Deng (Food Chemistry, 2025)

Integration of PG and NMM as a universal unlabeled, enzyme-free, luminescent-nanomaterial-free and catalysis-free dual-output system for versatile concurrent DNA logic computing and ratiometric fluorescent sensing - Jiawen Han; Yuwei Zhang; Xujuan Lv; Juan Wang; Daoqing Fan; Shaojun Dong (Chemical Engineering Journal, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Life cycle environmental and economic assessment of Phosphogypsum utilization in China - Lu Chen; Xiaoyu Luan; Feng Han; Yuwei Zhao; Huiying Yang; Long Zhang; Yongquan Yin; Wei Liu; Zhaojie Cui (Resources, Conservation and Recycling, 2025)

Environmentally relevant level of PFDA exacerbates intestinal inflammation by activating the cGAS/STING/NF-κB signaling pathway - Zhenyan Cui; Xiaoyu Yuan; Yuwei Wang; Zekun Liu; Xiaohong Fei; Kelie Chen; Han-Ming Shen; Yihua Wu; Dajing Xia (Science of The Total Environment, 2024)

Sponge-based FeS activated persulfate coupled with biodegradation for highly efficient removal of tetracycline: Batch and column validation - Shou Mei; Mengyao Han; Jintao Hao; Yuxuan Ye; Yuwei Deng; Luxin Liang; Ziyi Zhan; Rongling Wang; Xuanyuan Pei; Qiang Li; Zhenbin Wu; Fei Pan (Journal of Water Process Engineering, 2024)

Environmentally relevant concentrations of perfluorobutane sulfonate impair locomotion behaviors and healthspan by downregulating mitophagy in C. elegans - Yahui Shang; Kelie Chen; Heng Ni; Xiaoyu Zhu; Xiaoyu Yuan; Yuwei Wang; Xinxin Liu; Zhenyan Cui; Yuequn Niu; Yu Shi; Han Wu; Dajing Xia; et al. (Journal of Hazardous Materials, 2024)

Selective adsorption of arsenic by water treatment residuals cross-linked chitosan in co-existing oxyanions competition system - Huiping Zeng; Yuwei Zeng; He Xu; Weihua Zhao; Su Han; Jie Zhang; Dong Li (Environmental Research, 2024)

In-situ immobilization of Fe PBA in the zeolite structure for efficient degradation of benzalkonium chloride: Towards compressed reaction site loss and promoted PMS utilization - Qing Zhong; Ting Zhang; Zhi Huang; Longhui Su; Yuwei Xue; Ran Gao; Han Feng; Junming Hong (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Numerical studies on the effects of the hybrid cooling and dust suppression solution in hot fully-mechanized mining face - Song Xin; Xuefei Han; Qifei Sun; Menglin Li; Yuwei Wu; Zhen Zhang; Wenyu Yang (International Journal of Refrigeration, 2024)

Developing fine-tuned MOF membranes for highly efficient separation and adsorption of chemical pollutant in water - Jiatong Han; Donghui Xu; Yanyan Huang; Yuwei Hua; Xin Ding; Zhihao Lin; Jie Zhou; Huan Lin; Ge Chen; Jing Wang; Xiaomin Xu; Jia Liu; et al. (Chemical Engineering Journal, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

Technological readiness of commercial microalgae species for foods - Shufang Yang; Yuwei Fan; Yue Cao; Yuxin Wang; Haijin Mou; Han Sun (Critical Reviews in Food Science and Nutrition, 2024)

Completely blocking the feminization by replacing Limnodilus spp. with Artemia salina to feeding XY Zig-zag eel (Mastacembelus armatus) - Baoyue Lu; Xiaowen Xue; Zhide Yu; Linan Zhang; Jinlin Yang; Yuwei Feng; Yiman Chen; Chong Han; Xiaoli Yin; Hu Shu (Aquaculture, 2024)

Numerical Simulation of the Behavior of Caisson Based on Physical Modeling - Sifen Huang; Yuwei Han; Shuyi Li; Mi Zhou (Journal of Marine Science and Engineering, 2024)
Stiffened caissons are a new kind of offshore platform foundation which has been widely used in recent years. Stiffeners are employed to avoid buckling during the installation process. However, they also create a significant challenge in terms of understating the soil-flow patterns and corresponding installation resistance prediction. Although centrifuge and in situ tests can simulate the caisson installation process very well, their high costs prevent their widespread application. Model tests have been widely used in research on caisson behavior during installation, as they are convenient and cost less compared to centrifuge and prototype tests. However, the quantitative conclusions of the resulting predictions of installation resistance have some uncertainties because it is quite hard to strictly follow the similarity principle in 1 g model tests. Therefore, it is important to establish a method to calibrate the data from model tests, providing better estimates of caisson behavior in field tests. In our research, large deformation finite element (LDFE) analyses were conducted to provide insights into differences in the outcomes of caisson installation approaches between prototype tests and 1 g model tests. Prior to carrying out parametric studies, validations were conducted with good results. The results show that normalized soil strength significantly influences the behavior of caissons of various dimensions in 1 g model tests. In uniform clay, caissons exhibit consistent installation behavior; otherwise, they show significant differences. Based on systematic research, this paper reveals the mechanisms of the difference between model tests and prototype tests with different sizes of caissons and identifies the factors influencing these differences.

Overcoming genotypic dependency and bypassing immature embryos in wheat transformation by using morphogenic regulators - Ziru Zhou; Yawen Yang; Guo Ai; Miaomiao Zhao; Baozhu Han; Chunjie Zhao; Yiqian Chen; Yuwei Zhang; Hong Pan; Caixia Lan; Chao He; Qiang Li; et al. (Science China Life Sciences, 2024)

Enhanced reduction of graphene oxide via laser-dispersion coupling: Towards large-scale, low-defect graphene for crease-free heat-dissipating membranes in advanced flexible electronics - Jiawei Sun; Yuwei Xiong; Haiyang Jia; Longxiang Han; Wen Ye; Litao Sun (Science Bulletin, 2024)

Phylogeography and demographic history of macaques, fascicularis species group, in East Asia: Inferred from multiple genomic markers - Yanyan Zhou; Jundong Tian; Haijun Jiang; Mengya Han; Yuwei Wang; Jiqi Lu (Molecular Phylogenetics and Evolution, 2024)

Ecological impacts of the expansion of offshore wind farms on trophic level species of marine food chain - Lijing Wang; Bangguo Wang; Wenxi Cen; Rui Xu; Yuwei Huang; Xin Zhang; Yinghui Han; Yuanxun Zhang (Journal of Environmental Sciences, 2024)

Advances in the study of protein folding and endoplasmic reticulum-associated degradation in mammal cells - Hong Cao; Xuchang Zhou; Bowen Xu; Han Hu; Jianming Guo; Yuwei Ma; Miao Wang; Nan Li; Jun Zou (Journal of Zhejiang University-SCIENCE B, 2024)

Straw strip mulch improves soil moisture similar to plastic film mulch but with a higher net income - Jiantao Ma; Lei Chang; Yawei Li; Xuemei Lan; Wenning Ji; Jiantong Zhang; Fanxiang Han; Hongbo Cheng; Yuwei Chai; Shouxi Chai (Agriculture, Ecosystems & Environment, 2024)

Increased fine root production coupled with reduced aboveground production of plantations under a three-year experimental drought - Cuiting Wang; Yuan Sun; Xiaoming Zou; Han Y.H. Chen; Manuel Delgado-Baquerizo; Jingyan Yang; Guobing Wang; Yuwei Liu; Honghua Ruan (Science of The Total Environment, 2024)

Superb microplastics separation performance of graphene oxide tuned by laser bombardment - Jiawei Sun; Yuwei Xiong; Haiyang Jia; Longxiang Han; Kuibo Yin (Journal of Hazardous Materials, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

Selenium-based nanozyme as a fluorescence-enhanced probe and imaging for chlortetracycline in living cells and foods - Caimei Wu; Yuwei Zhang; Ming Han; Ruinan Zhang; Hua Li; Fali Wu; Aimin Wu; Xianxiang Wang (Food Chemistry, 2024)

Role of sulfate in regulating performance and metabolic mechanisms of bioelectrochemical up-flow anaerobic sludge blanket fed with methanolic wastewater - Yijing Gao; Bin Chen; Wanjiang Li; Yule Han; Zhaobin Liu; Yuwei Sun; Guihua Zhuo; Xueqin Lu; Samir Ibrahim Gadow; Weijie Hu; Guangyin Zhen (Journal of Cleaner Production, 2023)

Fungal necromass is reduced by intensive drought in subsoil but not in topsoil - Yuwei Liu; Xiaoming Zou; Han Y. H. Chen; Manuel Delgado‐Baquerizo; Cuiting Wang; Chen Zhang; Honghua Ruan (Global Change Biology, 2023)
The frequency and intensity of droughts worldwide are challenging the conservation of soil organic carbon (SOC) pool. Microbial necromass is a key component of SOC, but how it responds to drought at specific soil depths remains largely unknown. Here, we conducted a 3‐year field experiment in a forest plantation to investigate the impacts of drought intensities under three treatments (ambient control [CK], moderate drought [30% throughfall removal], and intensive drought [50% throughfall removal]) on soil microbial necromass pools (i.e., bacterial necromass carbon, fungal necromass carbon, and total microbial necromass carbon). We showed that the effects of drought on microbial necromass depended on microbial groups, soil depth, and drought intensity. While moderate drought increased total (+9.1% ± 3.3%) and fungal (+13.5% ± 4.9%) necromass carbon in the topsoil layer (0–15 cm), intensive drought reduced total (−31.6% ± 3.7%) and fungal (−43.6% ± 4.0%) necromass in the subsoil layer (15–30 cm). In contrast, both drought treatments significantly increased the BNC in the topsoil and subsoil. Our results suggested that the effects of drought on the microbial necromass of the subsoil were more pronounced than those of the topsoil. This study highlights the complex responses of microbial necromass to drought events depending on microbial community structure, drought intensity and soil depth with global implications when forecasting carbon cycling under climate change.

Influence of sulfate reducing bacteria cultured from the paddy soil on the solubility and redox behavior of Cd in a polymetallic system - Hui Huang; Yuwei Lv; Kunkun Tian; Yu Shen; Yongli Zhu; Haiying Lu; Ronghua Li; Jiangang Han (Science of The Total Environment, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Simulating the CCUS technology diffusion in thermal power plants: An agent-based evolutionary game model in complex networks - Jian Han; Qinliang Tan; Qingchao Ji; Yihan Li; Yuan Liu; Yuwei Wang (Journal of Cleaner Production, 2023)

Characterization of a novel nornicotine-degrading strain Mycolicibacterium sp. SMGY-1XX from a nornicotine-degrading consortium and preliminary elucidation of its biodegradation pathway by multi-omics analysis - Bingjun Dang; Wei Jia; Shuanglong Ma; Xiaoping Zhang; Yao Huang; Wuxing Huang; Dan Han; Kai Zhang; Fanchong Zhao; Yuwei Zhang; Zicheng Xu (Journal of Hazardous Materials, 2023)

Production optimization of refined bio-oil through plasma coupling catalysis and composite zeolite effect of Al-SBA-15/HZSM-5 - Yongsheng Fan; Yue Han; Jinjiao Zhu; Yuwei Chen; Yixi Cai; Weidong Zhao (Fuel, 2023)

Highly efficient activation of sulfite by p-type S-doped g-C3N4 under visible light for emerging contaminants degradation - Wenyuan Lu; Lijie Xu; Xianbao Shen; Liang Meng; Yuwei Pan; Ying Zhang; Jiangang Han; Xiang Mei; Weichuan Qiao; Lu Gan (Chemical Engineering Journal, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

Development of genetic sex markers of zig-zag eel (Mastacembelus armatus) by a NGS method - Weijian Qin; Chong Han; Jinlin Yang; Zhide Yu; Yuwei Feng; Yuxin Wu; Baoyue Lu; Mingxiang Cui; Hu Shu (Aquaculture, 2023)

Cooperative hydrogen- and halogen-bonding interaction promoted deep eutectic solvent-functionalized magnetic metal-organic framework for perfluoroalkyl iodides detection in edible oils - Yingyi Han; Chen Fan; Yaqi Yin; Yuwei Shan; Xueli Cao (Food Control, 2023)

A two-stage distributionally robust optimization model for geothermal-hydrogen integrated energy system operation considering multiple uncertainties - Ting Wang; Huiyu Han; Yuwei Wang (Environment, Development and Sustainability, 2023)

Adsorption of chlorophenols on activated pine sawdust-activated carbon from solution in batch mode - Yuwei Song; Yuanyuan Wang; Runping Han (Environmental Science and Pollution Research, 2022)

Kinetic and Thermodynamic Features of Pb(II) Removal From Aqueous Solution by Leonardite-Derived Humic Acid - Fande Meng; Yuwei Zhang; Yongbing Cai; Guodong Yuan; Feng X. Han (Water, Air, & Soil Pollution, 2021)

Oxalate Enhanced Organic Pollutant Removal with a UV/Fe0 System: Performance, Mechanisms, and Role of Oxalate - Yuwei Pan; Zhuoyu Bu; Xiang Li; Jiangang Han (Water, Air, & Soil Pollution, 2021)

Synergetic effect between adsorption and photodegradation on rGO/TiO2/ACF composites for dynamic toluene gaseous removal - Yuwei Li; Fang Liu; Meng Li; Xuye Wang; Xuejin Qi; Wei Li; Ming Xue; Yongqiang Wang; Fenglei Han (Environmental Science and Pollution Research, 2020)

Modulation of Beta Oscillations for Implicit Motor Timing in Primate Sensorimotor Cortex during Movement Preparation - Hongji Sun; Xuan Ma; Liya Tang; Jiuqi Han; Yuwei Zhao; Xuejiao Xu; Lubin Wang; Peng Zhang; Luyao Chen; Jin Zhou; Changyong Wang (Neuroscience Bulletin, 2019)

Development of a reverse genetics system for a feline panleukopenia virus - Nan Cheng; Yongkun Zhao; Qiuxue Han; Weijiao Zhang; Ji Xi; Yongle Yu; Hualei Wang; Guohua Li; Yuwei Gao; Songtao Yang; Weiquan Liu; Xianzhu Xia (Virus Genes, 2019)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

Comparison of waterborne and in ovo nanoinjection exposures to assess effects of PFOS on zebrafish embryos - Yabing Li; Zhihua Han; Xinmei Zheng; Zhiyuan Ma; Hongling Liu; John P. Giesy; Yuwei Xie; Hongxia Yu (Environmental Science and Pollution Research, 2015)

Soil Characteristics in Relation to Vegetation Communities in the Wetlands of Poyang Lake, China - Wang Xiaolong; Han Jingyi; Xu Ligang; Wan Rongrong; Chen Yuwei (Wetlands, 2014)